Treatment with metformin glycinate reduces SARS-CoV-2 viral load: An in vitro model and randomized, double-blind, Phase IIb clinical trial - Ventura-López, Claudia; Cervantes-Luevano, Karla; Aguirre-Sánchez, Janet S.; Flores-Caballero, Juan C.; Alvarez-Delgado, Carolina; Bernaldez-Sarabia, Johanna; Sánchez-Campos, Noemí; Lugo-Sánchez, Laura A.; Rodríguez-Vázquez, Ileana C.; Sander-Padilla, Jose G.; Romero-Antonio, Yulia; Arguedas-Núñez, María M.; et al. (Biomedicine & pharmacotherapy, 2022)
The health crisis caused by the new coronavirus SARS-CoV-2 highlights the need to identify new treatment strategies for this viral infection. During the past year, over 400 coronavirus disease (COVID-19) treatment patents have been registered; nevertheless, the presence of new virus variants has triggered more severe disease presentations and reduced treatment effectiveness, highlighting the need for new treatment options for the COVID-19. This study evaluates the Metformin Glycinate (MG) effect on the SARS-CoV-2 in vitro and in vivo viral load. The in vitro study was conducted in a model of Vero E6 cells, while the in vivo study was an adaptive, two-armed, randomized, prospective, longitudinal, double-blind, multicentric, and phase IIb clinical trial. Our in vitro results revealed that MG effectively inhibits viral replication after 48 h of exposure to the drug, with no cytotoxic effect in doses up to 100 µM. The effect of the MG was also tested against three variants of interest (alpha, delta, and epsilon), showing increased survival rates in cells treated with MG. These results are aligned with our clinical data, which indicates that MG treatment reduces SARS-CoV2-infected patients´ viral load in just 3.3 days and supplementary oxygen requirements compared with the control group. We expect our results can guide efforts to position MG as a therapeutic option for COVID-19 patients. •Metformin glycinate inhibits SARS-CoV-2 viral replication after 48 h of exposure.•MG increased survival in cells exposed to VOI (alpha, delta, and epsilon).•Patients treated with metformin glycinate reduces SARS-CoV2 viral load in 3.3 days.